2020
DOI: 10.15448/1980-8623.2020.3.34022
|View full text |Cite
|
Sign up to set email alerts
|

Tipologia circadiana de estudantes de Psicologia

Abstract: A tipologia circadiana é uma dimensão comportamental associada a preferências de hábitos diários. Contudo, este estudo objetivou avaliar a qualidade de sono e a sonolência excessiva de acadêmicos de Psicologia. Participaram deste estudo quase-experimental 56 estudantes com idade entre 17 e 34 anos. Utilizaram-se como instrumentos o Índice de Qualidade de Sono de Pittsburgh (PSQI), o Questionário de Matutinidade e Vespertinidade, a Escala de Sonolência de Karolinska e a Escala de Ritmo Social Breve. Após avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Similar results were found in this study; however, differences were observed for affable or loving behaviors in subjects with morning preference and, consequently, greater emotional stability for morning subjects. These results are similar to the findings 7 , which suggest that morning subjects are more conscientious than nocturnal subjects 13 . Refer that the sense of restraint and practical sense is consistent with practices of sensitivity and confidence of the kindness trait.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results were found in this study; however, differences were observed for affable or loving behaviors in subjects with morning preference and, consequently, greater emotional stability for morning subjects. These results are similar to the findings 7 , which suggest that morning subjects are more conscientious than nocturnal subjects 13 . Refer that the sense of restraint and practical sense is consistent with practices of sensitivity and confidence of the kindness trait.…”
Section: Discussionsupporting
confidence: 92%
“…However, a large part of the adult population is classified with an intermediate chronotype 4 . There is evidence to suggest that CT is influenced by individual factors, such as age and sex [5][6][7] , environmental factors, including exposure to light 8,9 , and also to cognitive skills and personality traits [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation